Neurologic recovery after ten minutes of absent cerebral blood flow at normothermia. (May 2021) - Pennel, Timothy; Beyersdorf, Friedhelm; Gates, Elliot; Zilla, Peter
Prolonged normothermic cardiac arrest is associated with a high incidence of neurological morbidity and mortality. Whole body temperature-controlled perfusion has been applied to limit reperfusion injury and minimize ischemia. We describe the full recovery of a patient after the application of rapid hypothermia following an intraoperative aortic rupture with ten minutes of absent cerebral blood flow.